The angiosperm flora of the Archipelago Juan Fernandez (Chile): Origin and dispersal - Bernardello, Gabriel Luis Mario (2006)
We review the hypothesized origin and the methods of arrival of the angiosperm colonists to the Juan Fernandez Islands. We also summarize the dispersal capabilities of the current flora, including data on fruit type, fruit length, and dispersal unit length, correlating these features with dispersal and establishment. Most species originated from South America, followed by Pantropical, Australian, New Zealand, and Pacific colonizers. Sea and land birds were the most important initial long-distance dispersal agents. Most colonizing species are hermaphroditic flowered, and thus all dispersal methods are represented among them. Monoecious, andromonoecious and gynomonoecious, dioecious, and polygamous species were mainly carried by birds. Most wind- and bird-pollinated colonizing genera arrived with birds as did most annual herbs and species with bright-colored flowers. In the current flora, the majority of the species have dry fruits. In monoecious, andromonoecious and gynomonoecious, and dioecious species, achenes predominate. Fleshy fruits are limited to perennials. Most species have medium to small dispersal units, and generally, the larger the flower, the larger the fruit. Large- and medium-sized dispersal units are common in shrubs and trees. Abiotic dispersal is common in the current flora, which may reflect the ancestral dispersal capability of the colonizers, or adaptation to the absence of a fauna to disperse seeds and fruits. Anemochorous and autochorous species are mainly perennial and have medium to large, unisexual flowers. Anemochorous species have small dispersal units and dull-colored flowers, whereas large dispersal units and brightly colored flowers are frequent in autochorous species. Medium-sized dispersal units are represented in autochorous or ornithochorous species. The establishment and evolution of this flora was previously discussed to have occurred with very few pollination and (or) reproductive options. This study suggests that elements associated with dispersal are also analogously limited.